Penguatan Struktur Diskrit dan Aritmatika Bilangan Bulat Sebagai Jembatan antara Teori dan Implementasi Digital Bagi Mahasiswa - Rozi, Syamsyida; Yurinanda, Sherli; Z, Gusmanely; Safitri, Yuliana; Sarmada, Sarmada (Institut Riset dan Publikasi Indonesia (IRPI), 2026)
Students of the Informatics Department at Jambi University continue to face difficulties in understanding discrete mathematics and integer arithmetic, despite both being fundamental components of algorithmic logic and programming. These challenges negatively affect their ability to construct and analyze algorithms. This community service activity aims to provide focused training to strengthen students’ understanding of discrete structure concepts and integer arithmetic, as well as their applications in digital system development. The training was delivered through an applied approach using project-based learning and relevant case studies. The activity was attended by 73 students of the Informatics Study Program, Faculty of Science and Technology, Jambi University. Based on the evaluation, 83.56% of participants reported being very satisfied with the training and stated that it was highly beneficial in reinforcing their understanding of discrete structures and integer arithmetic. Furthermore, post-activity test results showed that 54.80% of participants answered all questions correctly.